2021
DOI: 10.1101/2021.02.14.21251712
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ruling out SARS-CoV-2 infection using exhaled breath analysis by electronic nose in a public health setting

Abstract: Background: Rapid and accurate detection of SARS-CoV-2 infected individuals is crucial for taking timely measures and minimizing the risk of further SARS-CoV-2 spread. We aimed to assess the accuracy of exhaled breath analysis by electronic nose (eNose) for the discrimination between individuals with and without a SARS-CoV-2 infection. Methods: This was a prospective real-world study of individuals presenting to public test facility for SARS-CoV-2 detection by molecular amplification tests (TMA or RT-PCR). Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 35 publications
(47 reference statements)
0
28
0
Order By: Relevance
“…Several countries are at various stages of large clinical evaluations of instruments for breath detection of SARS-CoV-2 infection: examples include GeNose, BreathPass, SpiroNose, Brethonix. 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 Detection technologies employed include gas chromatography, different forms of mass spectrometry, and nanosensors to either detect volatile organic compounds or directly detect the virus. 91 There is a paucity of peer-reviewed literature evaluating large-scale clinical performance of the various assays.…”
Section: Other Novel Emerging Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several countries are at various stages of large clinical evaluations of instruments for breath detection of SARS-CoV-2 infection: examples include GeNose, BreathPass, SpiroNose, Brethonix. 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 Detection technologies employed include gas chromatography, different forms of mass spectrometry, and nanosensors to either detect volatile organic compounds or directly detect the virus. 91 There is a paucity of peer-reviewed literature evaluating large-scale clinical performance of the various assays.…”
Section: Other Novel Emerging Technologiesmentioning
confidence: 99%
“…92 However, another Dutch assay was found to have lower specificity of 82% when tested on asymptomatic persons and not long after it was launched its use was halted by Amsterdam’s Public Health Service after a concern about sensitivity. 93 , 94 Assays with good performance would have the potential to rapidly screen large populations as these assays screen individuals within minutes, but assays with high specificity would be more useful in low-prevalence settings such as Australia.…”
Section: Other Novel Emerging Technologiesmentioning
confidence: 99%
“…Six articles were included with a total of 4,093 participants. Patients’ recruited in the studies are individuals with suggestive symptoms of COVID-19 ( Wintjens et al, 2020 , Grassin-Delyle et al, 2021 , Ruszkiewicz et al, 2020 , de et al, 2021 ); acute respiratory distress syndrome (ARDS) patients requiring mechanical ventilation ( Grassin-Delyle et al, 2021 ); COVID-19 patients confirmed with RT-PCR ( Berna et al, 2021 , Shan et al, 2020 ), computed tomography (CT) and laboratory (antibody test) ( Shan et al, 2020 ). The study participants were then grouped into two based on their COVID-19 status (positive or negative).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies ( Ruszkiewicz et al, 2020 , de et al, 2021 , Shan et al, 2020 ) classified their subjects into specific sets to provide a thorough diagnostic evaluation. Ruszkiewicz et al (2020) categorized their study participants based on geographic locations ( Ruszkiewicz et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Currently available diagnostic techniques for COVID-19 are based on the detection of the viral gene, antigen, or human antibodies (serological test) and human metabolites [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Among these techniques, the detection of viral RNA sequences by reverse transcription polymerase chain reaction (RT-PCR), reverse transcription loop-mediated isothermal amplification (RT-LAMP), and reverse transcription quantitative polymerase chain reaction (RT-qPCR) have been the most reliable methods.…”
Section: Introductionmentioning
confidence: 99%